Ureterovesical anastomosis complications in kidney transplantation: definition, risk factor analysis, and prediction by quantitative fluorescence angiography with indocyanine green - Gerken, Andreas; Nowak, Kai; Meyer, Alexander; Kriegmair, Maximilian; Weiß, Christel; Krämer, Bernhard; Glossner, Pauline; Heller, Katharina; Karampinis, Ioannis; Kunath, Frank; Rahbari, Nuh Nabi; Schwenke, Kay; et al. (Journal of Clinical Medicine, 2022)
Ureteral stenosis and urinary leakage are relevant problems after kidney transplantation. A standardized definition of ureterovesical anastomosis complications after kidney transplantation has not yet been established. This study was designed to demonstrate the predictive power of quantitative indocyanine green (ICG) fluorescence angiography. This bicentric historic cohort study, conducted between November 2015 and December 2019, included 196 kidney transplantations. The associations between quantitative perfusion parameters of near-infrared fluorescence angiography with ICG and the occurrence of different grades of ureterovesical anastomosis complications in the context of donor, recipient, periprocedural, and postoperative characteristics were evaluated. Post-transplant ureterovesical anastomosis complications occurred in 18%. Complications were defined and graded into three categories. They were associated with the time on dialysis (p = 0.0025), the type of donation (p = 0.0404), and the number of postoperative dialysis sessions (p = 0.0173). Median ICG ingress at the proximal ureteral third was 14.00 (5.00-33.00) AU in patients with and 23.50 (4.00-117.00) AU in patients without complications (p = 0.0001, cutoff: 16 AU, sensitivity 70%, specificity 70%, AUC = 0.725, p = 0.0011). The proposed definition and grading of post-transplant ureterovesical anastomosis complications is intended to enable valid comparisons between studies. ICG Fluorescence angiography allows intraoperative quantitative assessment of ureteral microperfusion during kidney transplantation and is able to predict the incidence of ureterovesical anastomosis complications. Registration number: NCT-02775838.
Gesehen am 11.07.2023